New experimental heat capacity and enthalpy of formation of lithium cobalt oxide. (May 2015) - Gotcu-Freis, Petronela; Cupid, Damian M.; Rohde, Magnus; Seifert, Hans J.
Abstract : Graphical abstract: Highlights: LiCoO2 heat capacity was measured in the temperature range (160 to 953) K using DSC. Continuous/discontinuous methods were applied on different types of calorimeters. Enthalpy increment of LiCoO2 was determined using drop calorimetry at T = 974 K. Enthalpies of formation were evaluated from oxide melt drop solution calorimetry. Abstract: The heat capacity of LiCoO2 (O3-phase), constituent material in cathodes for lithium-ion batteries, was measured using two differential scanning calorimeters over the temperature range from (160 to 953) K (continuous method). As an alternative, the discontinuous method was employed over the temperature range from (493 to 693) K using a third calorimeter. Based on the results obtained, the enthalpy increment of LiCoO2 was derived from T = 298.15 K up to 974.15 K. Very good agreement was obtained between the derived enthalpy increment and our independent measurements of enthalpy increment using transposed temperature drop calorimetry at 974.15 K. In addition, values of the enthalpy of formation of LiCoO2 from the constituent oxides and elements were assessed based on measurements of enthalpy of dissolution using high temperature oxide melt drop solution calorimetry. The high temperature values obtained by these measurements are key input data in safety analysis and optimisation of the battery management systems which accounts for possible thermal runaway events.